Identification of Inhibitors in Lignocellulosic Slurries and Determination of Their Effect on Hydrocarbon-Producing Microorganisms - Yang, Shihui; Franden, Mary Ann; Yang, Qing; Chou, Yat-Chen; Zhang, Min; Pienkos, Philip T. (Frontiers in Bioengineering and Biotechnology, 2018)
The aim of this work was to identify inhibitors in pretreated lignocellulosic slurries, evaluate high-throughput screening strategies, and investigate the impact of inhibitors on potential hydrocarbon-producing microorganisms. Compounds present in slurries that could inhibit microbial growth were identified through a detailed analysis of saccharified slurries by applying a combination of approaches of HPLC, GC-MS, LC-DAD-MS and ICP-MS. Several high-throughput assays were then evaluated to generate toxicity profiles. Our results demonstrated that Bioscreen C was useful for analyzing bacterial toxicity but not for yeast. AlamarBlue reduction assay can be a useful high-throughput assay for both bacterial and yeast strains as long as medium components do not interfere with fluorescence measurements. In addition, this work identified two major inhibitors (furfural and ammonium acetate) for three potential hydrocarbon-producing bacterial species that include Escherichia coli, Cupriavidus necator, and Rhodococcus opacus PD630, which are also the primary inhibitors for ethanologens. This study was strived to establish a pipeline to quantify inhibitory compounds in biomass slurries and high-throughput approaches to investigate the effect of inhibitors on microbial biocatalysts, which can be applied for various biomass slurries or hydrolysates generated through different pretreatment and enzymatic hydrolysis processes or different microbial candidates.